A low-voltage cable

Through the coordinated design of the fractal twisted conductor layer, dynamic skeleton support layer and self-healing sheath, the contradiction between flexibility and strength of low-voltage cables under complex working conditions is resolved, and the long-term stable operation of the cables under frequent bending, torsion, stretching and pressure environments is achieved.

CN120527065BActive Publication Date: 2025-09-23江苏鸿翔电缆有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511016945.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-09-23
Estimated Expiration
2045-07-23

AI Technical Summary

Technical Problem

Existing low-voltage cables cannot operate stably for a long time under complex working conditions of frequent bending, twisting, stretching and compression. Traditional designs have the problem of being unable to achieve both rigidity and flexibility.

Method used

The fractal stranded conductor layer, dynamic skeleton support layer and self-healing sheath are collaboratively designed. The fractal stranded conductor is gradiently twisted with an inner layer of ultra-fine silver-plated copper wire, a middle layer of copper-clad aluminum wire and an outer layer of nickel-plated copper alloy wire. The support layer is composed of alternating oblique aramid fiber braids, shape memory polymers and carbon fiber composite tapes. Microcapsule self-healing agents and graphene nanosheets are added to the sheath layer.

Benefits of technology

The cable achieves long-life and stable operation under complex working conditions. It improves the mechanical strength and wear resistance of the cable by dispersing torsional stress, enhancing rigidity with shape memory polymer, and automatically repairing surface cracks with the self-healing sheath, thereby improving the cable's wear resistance and heat dissipation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120527065B_ABST
    Figure CN120527065B_ABST
Patent Text Reader

Abstract

The present invention provides a low-voltage cable, relating to the field of cable technology, including a conductor layer, a support layer, a shielding layer and a sheath layer, wherein the conductor layer is composed of multiple fractal stranded conductors, the fractal stranded conductors including an inner layer of ultrafine silver-plated copper wire, an intermediate layer of copper-clad aluminum wire and an outer layer of nickel-plated copper alloy wire; the support layer is coated on the outside of the conductor layer, including an inner support layer, a dynamic skeleton layer and an outer constraint layer, wherein the inner support layer is an obliquely wound aramid fiber braid, the dynamic skeleton layer is composed of a shape memory polymer and a carbon fiber composite tape alternately arranged, the outer constraint layer is a spirally wound silicone-glass fiber composite rope, and the shielding layer includes a tinned copper wire braid; the sheath layer is a thermoplastic polyurethane matrix, in which microcapsule self-healing agents are dispersed, the microcapsules contain siloxane prepolymers, and the thermoplastic polyurethane matrix also contains graphene nanosheets. Through the coordinated design of the fractal stranded conductor layer, the dynamic skeleton support layer, the shielding layer and the self-healing sheath, a comprehensive improvement in cable performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cables, in particular to a low-voltage cable. Background Art

[0002] In dynamic scenarios such as industrial robots, new energy equipment (such as wind turbine pitch systems and photovoltaic tracking brackets), and automated production lines, cables must operate stably and long-term under complex working conditions of frequent bending, twisting, stretching, and compression. However, existing low-voltage cable technology is limited by the contradiction between materials and structural design, and has the following problems:

[0003] 1. Traditional cables increase their compressive and tensile strength by adding metal armor layers or thicker-diameter conductors. However, such rigid structures significantly reduce flexibility, making the cable prone to sheath cracking or conductor fatigue fracture when bent.

[0004] 2. To improve flexibility, existing technologies often use fine-filament stranded conductors or soft sheath materials. However, fine-filament strands tend to loosen under torsional stress (for example, the S-shaped torsional path of a robot joint cable causes displacement of the conductor layer), while soft sheaths lack compressive support, exacerbating deformation of the internal structure.

[0005] Therefore, there is an urgent need for a cable solution that integrates material innovation and structural design to fundamentally resolve the synergistic contradictions between compression resistance, tension resistance, flexibility and torsional resistance, and to adapt to the needs of highly complex industrial environments. Summary of the Invention

[0006] In order to solve the technical problem that low-voltage cables cannot operate stably for a long time under complex working conditions such as frequent bending, twisting, stretching and compression in dynamic scenarios, the present invention provides a low-voltage cable.

[0007] The technical solutions provided by the embodiments of the present invention are as follows:

[0008] An embodiment of the present invention provides a low-voltage cable, comprising a conductor layer, a support layer, a shielding layer, and a sheath layer;

[0009] The conductor layer is composed of multiple strands of fractal stranded conductors, which include an inner layer of ultra-fine silver-plated copper wire, a middle layer of copper-clad aluminum wire and an outer layer of nickel-plated copper alloy wire;

[0010] The support layer is coated on the outside of the conductor layer and includes an inner support layer, a dynamic skeleton layer and an outer constraint layer, wherein the inner support layer is an obliquely wound aramid fiber braid with a braiding angle of 30 to 60 degrees, the dynamic skeleton layer is composed of shape memory polymer and carbon fiber composite tapes arranged alternately, and the glass transition temperature of the shape memory polymer is between 40°C and 60°C. The outer constraint layer is a spirally wound silicone-glass fiber composite rope, the diameter of the glass fiber monofilament in the composite rope is less than or equal to 15μm, and the silicone filling rate is not less than 85%. The shielding layer includes a tinned copper wire braid.

[0011] The sheath layer is a thermoplastic polyurethane matrix, in which a microcapsule self-healing agent is dispersed. The microcapsules contain silicone prepolymers, the particle size of the microcapsules is distributed between 30 μm and 150 μm, and are uniformly dispersed in the thermoplastic polyurethane matrix. The thermoplastic polyurethane matrix also contains graphene nanosheets, the number of graphene nanosheets does not exceed 5 layers, and the lateral size is 1 μm to 10 μm.

[0012] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:

[0013] This invention achieves comprehensive improvements in low-voltage cable performance through the coordinated design of a fractal stranded conductor layer, a dynamic skeleton support layer, a shielding layer, and a self-healing sheath. The gradient stranding direction of the fractal stranded conductor (left-handed in the inner layer, right-handed in the middle layer, and alternating SZ-shaped in the outer layer) disperses torsional stress, reduces internal friction, and extends the conductor's life in frequent bending or twisting scenarios. The dynamic skeleton layer alternates shape memory polymer (SMP) and carbon fiber composite tapes, utilizing the SMP's phase change properties (glass transition temperature of 40-60°C) to temporarily enhance cable rigidity under high temperatures or mechanical loads, resolving the "flexibility-strength trade-off" between traditional cables in dynamic environments. The siloxane prepolymer released from the microcapsules in the self-healing sheath automatically repairs surface cracks. Combined with the three-dimensional conductive and thermal network formed by the graphene nanosheets, this further enhances the sheath's wear resistance and heat dissipation efficiency, ensuring long-life, stable operation of the cable under complex operating conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0015] Figure 1 A schematic cross-sectional view of a low-voltage cable provided in an embodiment of the present invention.

[0016] Figure 2 A schematic diagram of a conductor layer of a low-voltage cable provided in an embodiment of the present invention Figure 1 .

[0017] Figure 3 A schematic diagram of a conductor layer of a low-voltage cable provided in an embodiment of the present invention Figure 2 .

[0018] Figure numerals: 1-conductor layer, 11-inner layer of ultrafine silver-plated copper wire, 12-middle layer of copper-clad aluminum wire, 13-outer layer of nickel-plated copper alloy wire, 2-support layer, 21-inner support layer, 22-dynamic skeleton layer, 23-outer constraint layer, 3-shielding layer, 4-sheath layer, 41-thermoplastic polyurethane matrix, 42-microcapsule self-healing agent.

[0019] As shown in the figure, in order to clearly implement the structure of the embodiment of the present invention, specific structures and devices are marked in the figure, but this is only for illustrative purposes and is not intended to limit the present invention to the specific structure, device and environment. According to specific needs, ordinary technicians in this field can adjust or modify these devices and environments. DETAILED DESCRIPTION

[0020] The technical solutions of the present invention are described below with reference to the accompanying drawings. It is also noted that, to provide a more detailed description, the following embodiments are best and preferred embodiments, and those skilled in the art may employ alternative implementations for certain known technologies. Furthermore, the accompanying drawings are intended only to provide a more detailed description of the embodiments and are not intended to limit the present invention.

[0021] like Figures 1 to 3 As shown, an embodiment of the present invention provides a low-voltage cable, wherein the conductor layer 1 is composed of multiple fractal twisted conductors, including an inner layer of ultra-fine silver-plated copper wire 11, an intermediate layer of copper-clad aluminum wire 12, and an outer layer of nickel-plated copper alloy wire 13. The arrangement of conductors of different materials and layers (fractal twisting) ensures that the cable can adapt to current transmission under different load conditions while providing low resistance. The diameter and twisting structure of each layer of conductors are carefully designed, wherein the twisting directions of each adjacent two conductors in the fractal spiral arrangement of the outer layer are opposite, which can effectively reduce electromagnetic interference and improve the electrical performance of the cable. The surface of the conductor layer 1 is coated with a nano-composite coating, which enhances the corrosion resistance and wear resistance of the conductor and extends the service life of the cable.

[0022] Furthermore, the support layer 2 is coated on the outside of the conductor layer 1 and consists of three parts: an inner support layer 21, a dynamic skeleton layer 22 and an outer constraint layer 23. The inner support layer 21 adopts an obliquely wound aramid fiber braided tape, and the braiding angle of the fiber is between 30° and 60°, which can effectively provide physical protection and improve the tensile strength of the cable. The dynamic skeleton layer 22 is made of shape memory polymer and carbon fiber composite tapes arranged alternately. The glass transition temperature of the shape memory polymer is between 40°C and 60°C. It can quickly restore its original shape when encountering temperature changes, thereby enhancing the overall strength of the cable, especially stress release in high temperature environments. The addition of carbon fiber not only enhances the tensile strength of the dynamic skeleton layer 22, but also improves the impact resistance of the cable. The outer constraint layer 23 is composed of a silicone-glass fiber composite rope, and the filling rate of silicone is not less than 85%, which provides further protection for the cable. The high strength characteristics of the glass fiber also ensure the ability to resist the external environment.

[0023] The shielding layer 3 comprises a tinned copper wire mesh, which effectively reduces the impact of external electromagnetic interference on the cable and ensures stable signal transmission. The sheath layer 4 utilizes a thermoplastic polyurethane matrix 41, within which microcapsule self-healing agents 42 are dispersed. These microcapsules contain silicone prepolymers, which automatically release the repair agent when cracks or damage occur on the cable surface, allowing for self-repair, preventing crack expansion and extending the service life of the cable. Graphene nanosheets are also incorporated into the thermoplastic polyurethane matrix 41. These graphene nanosheets can enhance the mechanical strength and wear resistance of the sheath layer 4, improving the scratch resistance and tensile strength of the cable.

[0024] The various layers of this low-voltage cable significantly improve the electrical performance, mechanical strength and service life of the cable through precise design and interaction. The fractal stranded conductor provides lower resistance and better electromagnetic shielding effect through optimized arrangement. The inner support layer 21 and the dynamic skeleton layer 22 of the support layer 2 effectively provide structural protection under high temperature and high pressure conditions, while the use of shape memory polymers improves the dynamic response capability. The outer constraint layer 23 ensures the stability and durability of the cable in the external environment. The design of the shielding layer 3 and the sheath layer 4 further ensures the safety of the cable, especially the introduction of the self-repair function, which ensures that the cable can recover quickly when damaged, reducing maintenance costs and usage risks. Overall, this design improves the application performance of low-voltage cables in high-demand environments.

[0025] In a possible implementation, the conductor layer 1 of the low-voltage cable adopts a fractal twisted structure to optimize the electrical and mechanical properties of the cable.

[0026] Specifically, the fractal stranded conductor consists of three layers of conductors made of different materials: the inner layer is ultra-fine silver-plated copper wire, the middle layer is copper-clad aluminum wire, and the outer layer is nickel-plated copper alloy wire. The diameters of the conductors in each layer are:

[0027] The diameter of the inner ultra-fine silver-plated copper wire 11 does not exceed 0.1 mm;

[0028] The diameter of the middle layer copper-clad aluminum wire 12 does not exceed 0.25 mm;

[0029] The diameter of the outer nickel-plated copper alloy wire 13 does not exceed 0.35 mm.

[0030] The fractal structure of the conductors is twisted, with the outer conductors arranged in a fractal spiral, ensuring that adjacent strands are twisted in opposite directions. This design effectively reduces electromagnetic interference, improves electrical performance, minimizes signal attenuation, and ensures cable stability in complex electrical environments.

[0031] Furthermore, each layer of the fractal stranded conductor is precisely designed in terms of the strand pitch, ensuring a good proportional relationship between the strand pitch of each layer of conductor and the outer diameter of the conductor, which are:

[0032] The ratio of the inner layer twist pitch to the conductor outer diameter is 4:1 to 6:1;

[0033] The ratio of the middle layer twist pitch to the conductor outer diameter is 7:1 to 9:1;

[0034] The ratio of outer layer lay pitch to conductor outer diameter is 9:1 to 12:1.

[0035] This pitch ratio design helps evenly distribute current, reducing stress concentration that can occur with a single pitch, thereby improving cable durability and reliability. Especially in high-temperature or high-current load environments, optimizing the twist pitch ratio can prevent local overheating, reduce resistance differences between conductors, and improve conductivity.

[0036] The outer conductors utilize an alternating fractal SZ spiral arrangement, which balances flexibility and resistance to loosening when the cable is bent. The twist direction of each adjacent conductor alternates for 3 to 5 twist pitches, and the twist angle of each twist section is set between 15° and 45°. This precise twisting design ensures stability during cable bending, preventing loosening or poor contact between conductors caused by excessive bending.

[0037] The precise pitch ratio and alternating twist design allow the cable to pass smoothly through bends, reducing damage caused by excessive bending. The alternating twist directions and appropriate twist angles of the outer conductors avoid stress concentration caused by a single twist pitch, thereby improving the cable's resistance to loosening and reducing physical damage and structural failure during long-term use. This design not only improves the cable's electrical transmission performance but also enhances its durability and reliability in various complex environments, providing technical support for the widespread application of high-performance low-voltage cables.

[0038] In one possible embodiment, the dynamic skeleton layer 22 in the low-voltage cable is a combination of shape memory polymer (SMP) and carbon fiber composite tape, aiming to achieve dynamic support and protection for the cable structure.

[0039] The dynamic skeleton layer 22 is composed of shape memory polymer (SMP) and carbon fiber composite tape. Specifically:

[0040] The mass ratio of shape memory polymer to carbon fiber composite tape is 1:1 to 1:3. The SMP's molecular segments are composed of styrene-butadiene block copolymer and polycaprolactone, with the mass ratio of styrene-butadiene block copolymer to polycaprolactone ranging from 2:1 to 4:1. This design enables the SMP's memory effect to be utilized at different temperatures, allowing the cable to adjust its shape according to environmental changes, improving its adaptability in various operating conditions.

[0041] The carbon fiber composite tape boasts a single-filament tensile modulus of no less than 200 GPa, providing exceptional strength and rigidity to enhance the cable's tensile strength. The carbon fibers are coated with a polytetrafluoroethylene (PTFE) coating with a thickness of 0.1 to 0.5 μm. This coating acts as a lubricant and insulator, reducing friction and environmental corrosion on the carbon fibers, further enhancing the cable's durability.

[0042] Furthermore, the design of the dynamic skeleton layer 22 enables the cable to maintain good stability when subjected to stress and temperature changes.

[0043] Shape memory polymers undergo phase transitions when exposed to temperature changes, typically exhibiting a significant change in strength upon reaching the glass transition temperature. This phase change response time ranges from 0.5 to 3 seconds, meaning the cable can respond to changes in external mechanical loads in a relatively short period of time. The carbon fiber composite tape provides strong mechanical support, particularly when the cable is stretched and bent. The high modulus of the carbon fiber ensures the cable's tensile strength and prevents excessive deformation.

[0044] When the temperature reaches the glass transition temperature, the tensile strength of SMP increases to 1.5 to 2.5 times its normal value. This change provides strong support under extreme conditions, allowing the dynamic skeleton layer 22 to effectively suppress the displacement of the conductor layer 1, especially when the cable is subjected to external forces or bent, preventing relative movement of the conductors.

[0045] Among them, the shape memory effect of SMP ensures that the cable can automatically adjust its shape according to the external environment, while the carbon fiber composite tape provides the necessary structural rigidity, so that the cable has good flexibility and support capabilities under normal conditions, and can also cope with drastic temperature changes and mechanical loads.

[0046] The design of this dynamic skeleton layer 22, by combining SMP and carbon fiber composite tape, not only improves the mechanical properties of the cable, but also ensures the stability and reliability of the cable under complex working conditions, and has high practical value.

[0047] In one possible embodiment, the sheath layer 4 in the low-voltage cable is designed with a microcapsule self-healing agent 42 to enhance the cable's damage resistance, especially to enable it to automatically repair itself after cracks are formed and maintain the integrity of the conductive network.

[0048] Specifically, the microcapsule self-repairing agent 42 in the sheath layer 4 is composed of two parts:

[0049] Siloxane prepolymer: Siloxane prepolymer accounts for 70% to 90% of the total mass of the microcapsules. Siloxane prepolymer is a substance that chemically repairs cracks or damage in the cable sheath. Its excellent fluidity and chemical activity allow it to effectively fill and repair cracks.

[0050] Thermoplastic polyurethane matrix 41: The thermoplastic polyurethane matrix 41 has a hardness of 80A to 90A (Shore A), indicating good flexibility and wear resistance, making it suitable as the base material for the jacket layer 4. Graphene nanosheets comprise 5% to 15% of the matrix by mass. The introduction of graphene further enhances the mechanical strength, electrical conductivity, and thermal conductivity of the matrix.

[0051] When the microcapsules rupture, the silicone prepolymer quickly fills the cracks and solidifies, repairing the cracks in the sheath layer 4. Simultaneously, the distribution of graphene nanosheets within the thermoplastic polyurethane matrix 41 helps improve the material's electrical and thermal conductivity. Graphene's conductive properties help maintain the integrity of the cable's conductive network, preventing electrical performance degradation due to localized damage or overheating.

[0052] When cracks appear in the sheath layer 4 and the silicone prepolymer begins to repair them, the graphene nanosheets also utilize their excellent thermal conductivity to help disperse the heat generated by local overheating, thereby preventing further damage to the sheath layer 4. In this way, graphene not only facilitates the repair process but also ensures the cable's electrical conductivity and thermal stability after damage.

[0053] During the manufacturing process of the sheath layer 4, the microcapsule self-healing agent 42 is evenly distributed in the thermoplastic polyurethane matrix 41. The microcapsules remain intact under normal use, but when cracks or damage appear on the cable surface, the microcapsules rupture and release the silicone prepolymer to fill and repair the cracks.

[0054] The addition of graphene nanosheets not only enhances the physical strength of the matrix, but also improves the electrical and thermal conductivity of the cable. Especially when the cable is overloaded or the external temperature rises, graphene can effectively prevent local overheating of the cable and maintain the overall performance of the cable.

[0055] Through the synergistic effect of microcapsule self-healing agent 42 and graphene nanosheets, not only the repair ability and durability of the cable sheath are improved, but also the conductivity, thermal stability and safety of the cable are effectively improved, which has significant application value.

[0056] In one possible implementation, the design of a low-voltage cable involves the synergistic effect of graphene nanosheets and carbon nanotubes. By carboxylating the graphene nanosheets and connecting them to the carbon nanotubes through a special structure, a cross-scale network structure with high strength and high thermal conductivity can be formed within the low-voltage cable, improving the cable's performance.

[0057] Specifically, in this design, the edges of the graphene nanosheets are carboxylated, resulting in surface carboxyl groups (-COOH). The density of these carboxyl groups ranges from 0.5 mmol / g to 2 mmol / g. The introduction of carboxyl groups can significantly enhance the interfacial bonding between graphene and other materials, particularly its interaction with carbon nanotubes, providing stronger chemical bonding and physical contact.

[0058] Graphene nanosheets and carbon nanotubes form a three-dimensional network structure through π-π stacking and chemical bonding. Specifically, the carboxyl groups on the edges of the graphene sheets form chemical bonds with the surface of the carbon nanotubes. Simultaneously, the π-electron cloud of the graphene and the π-electron cloud of the carbon nanotubes undergo π-π stacking, forming a strong and stable three-dimensional network. This structure enables the graphene and carbon nanotubes to form a cross-scale network within the cable matrix, enhancing both electrical and thermal conductivity.

[0059] Carbon nanotubes range in length from 1μm to 5μm, with an outer diameter of 5nm to 50nm. This size range ensures a high surface area and excellent mechanical strength. The mass ratio of carbon nanotubes to graphene ranges from 3:1 to 5:1, which helps achieve balanced mechanical and electrical properties in the composite material. The carbon nanotubes provide structural reinforcement and electrical conductivity in the cable, while the three-dimensional network they form with graphene makes the cable material stronger and more efficient.

[0060] Graphene nanosheets and carbon nanotubes form a compact three-dimensional network at the microscopic level through π-π stacking and chemical bonding. This structure ensures the stability of the cable material under stress and temperature fluctuations. The combination of graphene and carbon nanotubes not only improves the electrical and thermal conductivity of the cable, but also enables the cable to maintain its structural integrity despite external mechanical stress or temperature fluctuations.

[0061] During the manufacturing process, the graphene nanosheets are first carboxylated to ensure their surface is highly hydrophilic and chemically active, enabling better bonding with the carbon nanotubes. Next, the carbon nanotubes and carboxylated graphene nanosheets are mixed in a specific ratio through physical or chemical methods (such as solution mixing or chemical vapor deposition) and evenly distributed within the cable's polymer matrix. This process creates a stable three-dimensional network of carbon nanotubes and graphene nanosheets, enhancing the cable's overall performance.

[0062] Through the orderly arrangement and combination of carboxylated graphene and carbon nanotubes, the cable has not only significantly improved its electrical and thermal conductivity, but also made significant progress in mechanical properties and stability.

[0063] In one possible embodiment, the nanocomposite coating coated on the surface of the conductor layer 1 of the low-voltage cable contains graphene, carbon nanotubes and epoxy resin, and is designed with a structure in which vertically oriented carbon nanotubes are embedded between graphene sheets, which has significant advantages, especially in terms of electron transmission performance.

[0064] Specifically, the coating is composed of graphene, carbon nanotubes, and epoxy resin, with graphene accounting for 50% to 70% of the coating mass, carbon nanotubes for 20% to 40%, and epoxy resin for 5% to 15%. Graphene has excellent electrical conductivity, while the addition of carbon nanotubes enhances the mechanical strength and electrical conductivity of the coating, while the epoxy resin provides adhesion and stability.

[0065] The carbon nanotubes are embedded between the graphene sheets in a vertical orientation, with the deviation in orientation angles not exceeding 10 degrees. The advantage of this structural design is that the combination of carbon nanotubes and graphene provides a good electron transmission channel, reducing the resistance to electron transmission, allowing current to pass through the coating more efficiently, thereby reducing current loss.

[0066] The surface of the carbon nanotubes is treated with plasma to form oxygen-containing functional groups. These functional groups can enhance the interfacial bonding between the carbon nanotubes and the graphene sheets, further strengthening the adhesion between the coating and the conductive layer 1, thereby ensuring that the coating will not fall off during use and improving the stability and durability of the coating.

[0067] The coating thickness is controlled between 8μm and 25μm, and the surface roughness Ra value is less than or equal to 0.1μm. This makes the coating surface smoother, reduces friction and current loss, and helps improve the electrical performance and transmission efficiency of the cable.

[0068] The coating and the conductor layer 1 are bonded together by chemical bonds. This bonding method enhances the adhesion of the coating, avoids the problem of the coating falling off due to thermal expansion or mechanical stress during operation, and ensures that the cable has good electrical and mechanical properties during long-term use.

[0069] Through the above design, the coating of the low-voltage cable has a significant improvement in electron transmission performance. The close bonding between the vertically oriented carbon nanotubes and graphene sheets significantly reduces the electron transmission resistance, optimizes the flow path of the current, and thus reduces the power loss. The oxygen-containing functional groups treated with plasma improve the bonding force between the coating and the conductor layer 1, and enhance the durability and stability of the coating. The smooth surface coating also effectively reduces friction, reduces the possibility of heat generation, and ensures the reliability of the cable during long-term operation. In addition, through the method of chemical bonding, the bonding between the coating and the conductor layer 1 is more firm and not easy to fall off, further enhancing the durability and electrical safety of the cable.

[0070] In one possible embodiment, the outer constraint layer 23 of the low-voltage cable uses a silicone-glass fiber composite rope with an optimized structural design, which can provide higher high-temperature stability and creep resistance to adapt to dynamic deformation in extreme temperature environments.

[0071] Specifically, the composite rope is made of high-temperature resistant silicone rubber (silicone) and glass fiber monofilament. Silicone rubber has excellent high-temperature resistance, with a temperature range of -50°C to 200°C, which can adapt to the extreme temperature working environments of most cables.

[0072] Nano-alumina particles are dispersed within the silica gel matrix. The particles range in size from 10nm to 100nm, accounting for 1% to 5% by weight. These nano-alumina particles not only increase the thermal conductivity of the silica gel but also improve its resistance to thermal aging, enabling the outer constraint layer 23 to maintain stable performance in high-temperature environments and avoid thermal degradation.

[0073] The elongation at break of the glass fiber monofilament is controlled within 3%, which indicates that the glass fiber has high rigidity and can maintain a good shape under stress and is not easy to deform. This characteristic of glass fiber ensures the structural stability of the composite rope in long-term use.

[0074] The surface of the glass fiber monofilament is treated with a silane coupling agent, with the coating amount of the coupling agent being 0.1% to 0.5% of the glass fiber mass. The function of the silane coupling agent is to strengthen the adhesion between the glass fiber and the silicone matrix, prevent slippage or separation at the interface between the glass fiber and the silicone, and ensure the overall mechanical strength and durability of the composite rope.

[0075] The silicone-glass fiber composite rope is spirally wound with a winding angle controlled between 30 and 60 degrees, and a spacing of 0.5 to 2 mm between adjacent ropes. This winding structure provides the composite rope with high mechanical strength and excellent compressive resistance. The designed winding angle ensures uniform stress distribution when the composite rope is subjected to load, reducing the risk of localized damage.

[0076] The tensile strength of the composite rope is not less than 200MPa, which ensures that the composite rope can maintain its good shape under dynamic load and will not break or loose due to tension. The high tensile strength provides the composite rope with additional safety and stability.

[0077] The design of the silicone-glass fiber composite rope significantly improves the stability, durability and reliability of the cable in extreme temperature environments, especially under high temperature and dynamic load conditions, ensuring the long-term and safe operation of the cable.

[0078] In a possible embodiment, the shielding layer 3 of the low-voltage cable adopts a combination of a tinned copper wire braid and a porous ceramic isolation layer. This design can improve the shielding effectiveness of the cable while also enhancing its mechanical strength and thermal conductivity.

[0079] Specifically, the tinned copper wire mesh of shielding layer 3 has a coverage rate of at least 80%, ensuring the shielding effectiveness of the cable. The copper wire diameter is controlled between 0.05mm and 0.15mm. This wire diameter not only provides good electromagnetic shielding effect, but also ensures a certain degree of flexibility of the cable to adapt to different application requirements.

[0080] The choice of tinned copper wire gives the copper wire a certain advantage in corrosion resistance, extending the service life of the cable.

[0081] A porous ceramic isolation layer is placed outside the copper wire mesh. The porosity of this ceramic layer is 40% to 60%, and the pore size is controlled between 5μm and 20μm. This porous structure effectively absorbs electromagnetic waves and reduces electromagnetic interference. The scattering effect of the pores also disperses mechanical stress, preventing damage to the cable shield layer 3 due to external forces.

[0082] Ceramic material options include aluminum oxide, silicon nitride or silicon carbide, all of which are materials with high temperature stability and strong resistance to mechanical shock, which ensures that the isolation layer can maintain its function in high temperature or strong environment.

[0083] The thickness of the ceramic layer is set between 0.1mm and 0.3mm, which not only ensures good electromagnetic wave absorption ability but also avoids weight and rigidity problems caused by excessive thickness.

[0084] The porous ceramic isolation layer and the tinned copper wire mesh are bonded together with an epoxy adhesive having a thickness of 10 to 50 μm. This adhesive layer ensures a tight bond between the ceramic isolation layer and the copper wire mesh, preventing them from falling off or slipping, and maintaining the stability and reliability of the shielding layer 3.

[0085] The adhesive is doped with carbon nanotubes, at a concentration of 0.1% to 1% by weight. The addition of carbon nanotubes significantly improves the adhesive's thermal conductivity, preventing localized temperature rise during cable operation that can lead to a decrease in shielding effectiveness. The carbon nanotubes effectively promote heat conduction, ensuring that the shielding layer 3 maintains its electromagnetic shielding function even in high-temperature environments.

[0086] The design combines tinned copper wire mesh with a porous ceramic insulation layer, effectively enhancing the cable's electromagnetic shielding performance while also improving its reliability and durability in terms of high temperatures, mechanical stress, and thermal management. This design ensures long-term stable operation of low-voltage cables in complex environments.

[0087] In one possible embodiment, a piezoelectric ceramic particle layer is added to the sheath layer 4 of the low-voltage cable. This design can monitor the deformation state of the cable in real time, detect abnormalities, and provide repair functions.

[0088] Specifically, the piezoelectric ceramic particles are made of lead zirconate titanate (PZT), a material with excellent piezoelectric properties and a high Curie temperature. The particle size distribution is controlled between 1μm and 10μm to ensure good electrical signal response characteristics. The particles have a Curie temperature range of 150°C to 350°C, allowing them to maintain effective piezoelectric effect even at higher temperatures.

[0089] The piezoelectric ceramic particles are dispersed in the thermoplastic polyurethane matrix 41 at a ratio of 3% to 10% by mass. This ratio ensures effective distribution of the particles, which not only ensures the sensitivity of the piezoelectric effect but also does not affect the flexibility and mechanical properties of the polyurethane matrix.

[0090] The spacing between the piezoelectric ceramic particles is set to 5μm to 50μm, ensuring effective electrical signal transmission between the particles and avoiding signal weakening caused by excessive particle spacing.

[0091] To improve the insulation and durability of the piezoelectric ceramic particles, each particle is coated with a polyvinylidene fluoride (PVDF) insulating layer. The thickness of the PVDF layer is set between 0.1μm and 1μm, providing sufficient electrical isolation to prevent short circuits between particles.

[0092] The crystallinity of PVDF is not less than 50%, which improves its electrical insulation performance and mechanical strength, so that the coating can better protect the piezoelectric ceramic particles during the use of the cable and ensure its long-term stable operation.

[0093] When a cable is subjected to external mechanical forces (such as bending, torsion, or vibration), the piezoelectric ceramic particles deform and generate electric charges. The output signal of these charges is positively correlated with the mechanical stress (such as torsion angle and bending amplitude) experienced by the cable. By monitoring these electrical signals, real-time feedback on the cable's deformation status can be obtained. This signal monitoring can detect abnormal torsion, overload, or fatigue damage in the cable, and even predict the cable's service life.

[0094] When the sheath deforms and develops microcracks due to external mechanical forces, the piezoelectric effect generates an electrical signal that triggers an electric field, activating the release of a microcapsule repair agent. Driven by the electric field, the repair agent rapidly fills the cracks and repairs the sheath damage. This repair mechanism significantly enhances the cable's self-healing capabilities, preventing damage caused by microcrack propagation and extending its service life.

[0095] The low-voltage cable adds piezoelectric ceramic particles to the sheath layer 4 and adopts a microcapsule repair agent release mechanism, which not only enables real-time monitoring and abnormality detection of the cable, but also effectively extends the service life of the cable and improves its damage resistance. These designs will greatly enhance the reliability and self-repair ability of the cable in complex working environments.

[0096] In one possible embodiment, the low-voltage cable introduces a "dynamic skeleton layer 22" in the structural design. This layer is composed of a specific proportion of shape memory polymer (SMP) and is composited with the inner support layer 21 and the outer constraint layer 23 using a hot pressing process, thereby achieving enhanced structural stability under impact or temperature change environments.

[0097] Specifically, this layer is made of a shape memory polymer, whose molecular segments include styrene-butadiene block copolymer and polycaprolactone. These two materials provide good rigid support and excellent memory recovery properties, respectively. By mixing styrene-butadiene block copolymer and polycaprolactone in a mass ratio of 2:1 to 4:1, the thermal response characteristics of the material are controlled, allowing the skeleton layer to quickly transition from soft to rigid upon heating, while maintaining a balance between mechanical support and deformability.

[0098] Process parameter control: The dynamic skeleton layer 22 is composited with the inner support layer 21 and the outer constraint layer 23 through a hot pressing process. The hot pressing temperature is controlled between 100°C and 150°C, corresponding to the glass transition temperature range of styrene-butadiene block copolymer and polycaprolactone, which facilitates the alignment of molecular chains and activation of the composite interface.

[0099] The hot pressing pressure is set to 5MPa to 15MPa, which can ensure that the layers are fully fitted together to form a stable and firm interface bond with a bonding strength of no less than 5MPa.

[0100] The hot pressing time is set in an appropriate range according to the material thickness and equipment performance, ensuring that the thickness of the dynamic skeleton layer 22 is controlled within 0.2mm to 0.8mm, meeting the requirements of the flexible cable structure without affecting the overall bending performance.

[0101] Below the glass transition temperature (such as at room temperature), the storage modulus of the skeleton layer reaches 1GPa to 3GPa, showing high rigidity support capability and providing sufficient mechanical stability for the cable.

[0102] Once the cable is affected by temperature rise, such as external mechanical load or impact causing local temperature rise, when the SMP reaches above the glass transition temperature, the storage modulus drops to 10MPa to 50MPa, and the material becomes soft and deformable. At this time, the cable structure can effectively buffer external impact.

[0103] The dynamic skeleton layer 22 composed of styrene-butadiene block copolymer-polycaprolactone shape memory polymer is combined with a hot pressing process for multi-layer composite. This not only enables the cable to have adaptive rigid-flexible switching capabilities, but also significantly improves its impact resistance and structural stability. It is a key innovation in the design of high-performance low-voltage cables.

[0104] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:

[0105] In this invention, the optimized design of each layer, particularly the self-healing and high-strength protective features of the support layer 2 and jacket layer 4, not only improves the cable's mechanical strength but also enhances its durability and safety. The application of a nanocomposite coating on the conductor layer 1 effectively prevents corrosion, while the combination of shape memory polymer and carbon fiber in the support layer 2 enhances the cable's tensile and impact resistance in harsh environments. The entire cable system boasts a compact structure, effectively resisting external shocks and internal electrical loads, ensuring the long-term, stable operation of the low-voltage cable.

[0106] The present invention encompasses any alternatives, modifications, equivalents, and solutions that fall within the spirit and scope of the present invention. While specific details are described in detail in the preferred embodiments to provide a thorough understanding of the present invention, those skilled in the art will be able to fully understand the present invention without these details. Furthermore, to avoid unnecessary confusion regarding the essence of the present invention, well-known methods, processes, procedures, components, and circuits have not been described in detail.

[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A low voltage cable, characterized in that: It comprises a conductor layer (1), a support layer (2), a shielding layer (3) and a sheath layer (4); The conductor layer (1) is composed of multiple strands of fractal twisted conductors, wherein the fractal twisted conductors include an inner layer of ultra-fine silver-plated copper wires (11), an intermediate layer of copper-clad aluminum wires (12), and an outer layer of nickel-plated copper alloy wires (13); The support layer (2) is coated on the outside of the conductor layer (1), and includes an inner support layer (21), a dynamic skeleton layer (22) and an outer constraint layer (23), wherein the inner support layer (21) is an obliquely wound aramid fiber braid with a braiding angle of 30 to 60 degrees, the dynamic skeleton layer (22) is composed of shape memory polymer and carbon fiber composite tapes arranged alternately, and the glass transition temperature of the shape memory polymer is between 40°C and 60°C, the outer constraint layer (23) is a spirally wound silicone-glass fiber composite rope, the diameter of the glass fiber monofilament in the composite rope is less than or equal to 15μm, and the silicone filling rate is not less than 85%, and the shielding layer (3) includes a tinned copper wire braid. The sheath layer (4) is a thermoplastic polyurethane matrix (41), in which a microcapsule self-healing agent (42) is dispersed. The microcapsules contain silicone prepolymers, and the particle size of the microcapsules is distributed between 30 μm and 150 μm, and are uniformly dispersed in the thermoplastic polyurethane matrix (41). The thermoplastic polyurethane matrix (41) also contains graphene nanosheets, and the number of layers of the graphene nanosheets does not exceed 5, and the lateral size is 1 μm to 10 μm.

2. The low-voltage cable according to claim 1, characterized in that The fractal stranded conductor has an inner layer of ultra-fine silver-plated copper wire (11) with a diameter less than or equal to 0.1 mm, an intermediate layer of copper-clad aluminum wire (12) with a diameter less than or equal to 0.25 mm, an outer layer of nickel-plated copper alloy wire (13) with a diameter less than or equal to 0.35 mm, and the twisting directions of two adjacent conductors in the fractal spiral arrangement of the outer conductor are opposite; The ratio of the inner layer twist pitch of the fractal stranded conductor to the outer diameter of the conductor is 4:1 to 6:1, the ratio of the middle layer twist pitch to the outer diameter of the conductor is 7:1 to 9:1, and the ratio of the outer layer twist pitch to the outer diameter of the conductor is 9:1 to 12:1; In the alternating SZ fractal spiral arrangement of the outer conductors, the alternating period of the twist directions of adjacent conductors is 3 to 5 twist pitch lengths, and the torsion angle of each twist direction is 15 degrees to 45 degrees.

3. The low-voltage cable according to claim 2, characterized in that The mass ratio of the shape memory polymer to the carbon fiber composite tape in the dynamic skeleton layer (22) is 1:1 to 1:3, the molecular chain segments of the shape memory polymer include styrene-butadiene block copolymer and polycaprolactone, wherein the mass ratio of the styrene-butadiene block copolymer to the polycaprolactone is 2:1 to 4:1; The tensile modulus of the carbon fiber monofilament in the carbon fiber composite tape is not less than 200 GPa, and the surface of the carbon fiber is coated with a polytetrafluoroethylene coating with a coating thickness of 0.1 μm to 0.5 μm; The phase change response time of the dynamic skeleton layer (22) is 0.5 seconds to 3 seconds, and when the temperature reaches the glass transition temperature, the tensile strength is increased to 1.5 times to 2.5 times the normal value.

4. The low-voltage cable according to claim 3, characterized in that The mass proportion of the siloxane prepolymer in the microcapsule self-healing agent (42) of the sheath layer (4) is 70% to 90% of the total mass of the microcapsules, the hardness of the thermoplastic polyurethane matrix (41) is 80A to 90A, and the mass proportion of the graphene nanosheets in the thermoplastic polyurethane matrix (41) is 5% to 15%.

5. The low-voltage cable according to claim 4, characterized in that The edges of the graphene nanosheets are carboxylated, the density of the carboxyl functional groups is 0.5 mmol / g to 2 mmol / g, and the graphene sheets form a three-dimensional network structure with the carbon nanotubes through π-π bonds between the layers; The mass ratio of the graphene nanosheets to the carbon nanotubes is 3:1 to 5:1, the carbon nanotubes are 1 μm to 5 μm in length, and have an outer diameter of 5 nm to 50 nm.

6. The low-voltage cable according to claim 5, characterized in that The surface of the conductor layer (1) is coated with a nanocomposite coating, which is composed of graphene, carbon nanotubes and epoxy resin, wherein the graphene accounts for 50% to 70% of the coating mass, the carbon nanotubes account for 20% to 40%, and the epoxy resin accounts for 5% to 15%; The carbon nanotubes are embedded between graphene sheets in a vertically oriented manner with an orientation angle deviation of no more than 10 degrees, and the surfaces of the carbon nanotubes are treated with plasma to form oxygen-containing functional groups; The coating has a thickness of 8 μm to 25 μm, a surface roughness Ra value of less than or equal to 0.1 μm, and the coating is bonded to the conductor layer (1) through a chemical bond.

7. The low-voltage cable according to claim 6, characterized in that The spiral winding angle of the silica gel-glass fiber composite rope of the outer constraint layer (23) is 30 to 60 degrees, the spacing between adjacent ropes is 0.5 mm to 2 mm, and the tensile strength of the composite rope is not less than 200 MPa; The silica gel is a high-temperature resistant silicone rubber with a temperature resistance range of -50°C to 200°C, and nano-aluminum oxide particles are dispersed in the silica gel, with a particle size of 10nm to 100nm and a mass ratio of 1% to 5%; The breaking elongation of the glass fiber monofilament does not exceed 3%, and the surface is treated with a silane coupling agent, and the coating amount of the coupling agent is 0.1% to 0.5% of the mass of the glass fiber.

8. The low-voltage cable according to claim 7, characterized in that The shielding layer (3) has a tinned copper wire braided mesh coverage of not less than 80%, a braided mesh wire diameter of 0.05 mm to 0.15 mm, and a porous ceramic isolation layer is provided on the outside of the braided mesh; The porous ceramic isolation layer has a porosity of 40% to 60%, a pore size of 5 μm to 20 μm, a ceramic material selected from a group consisting of aluminum oxide, silicon nitride, and silicon carbide, and a ceramic layer thickness of 0.1 mm to 0.3 mm. The porous ceramic isolation layer and the tinned copper wire mesh are bonded by epoxy adhesive, the thickness of the adhesive is 10 μm to 50 μm, and the adhesive is doped with carbon nanotubes, and the doping amount is 0.1% to 1% of the adhesive mass.

9. The low-voltage cable according to claim 8, characterized in that The inner surface of the sheath layer (4) is provided with a piezoelectric ceramic particle layer, wherein the piezoelectric ceramic particles are lead zirconate titanate material, have a particle size distribution between 1 μm and 10 μm, and are dispersed in the thermoplastic polyurethane matrix (41) at a mass ratio of 3% to 10%; The piezoelectric ceramic particles have a Curie temperature of 150° C. to 350° C., a piezoelectric constant d33 value of not less than 200 pC / N, and a particle spacing of 5 μm to 50 μm; The surface of the piezoelectric ceramic particles is coated with a polyvinylidene fluoride insulating layer, the thickness of the insulating layer is 0.1 μm to 1 μm, and the crystallinity of the PVDF is not less than 50%.

10. The low-voltage cable according to claim 9, characterized in that In the dynamic skeleton layer (22), the molecular chain segments of the shape memory polymer include styrene-butadiene block copolymer and polycaprolactone, wherein the mass ratio of the styrene-butadiene block copolymer to the polycaprolactone is 2:1 to 4:1; The storage modulus of the shape memory polymer is 1 GPa to 3 GPa below the glass transition temperature and 10 MPa to 50 MPa above the glass transition temperature; The thickness of the dynamic skeleton layer (22) is 0.2 mm to 0.8 mm, and the dynamic skeleton layer (22) is composited with the inner support layer (21) and the outer constraint layer (23) through a hot pressing process, with the composite interface bonding strength being not less than 5 MPa. The hot pressing temperature is 100° C. to 150° C., and the pressure is 5 MPa to 15 MPa.

Citation Information

Patent Citations

  • Flat cable, rotating connector using the same, and method for producing flat cable

    CN109196603A

  • Self-repairing cable

    WO2016132127A2